Penyuluhan Tentang Gastritis Pada Masyarakat Di Dusun II Desa Sumber Sari Wilayah Kerja Puskesmas Bukit Sari, Kecamatan Kabawetan, Kabupaten Kepahiang - Ayu, Anggra; Septiya, Septiya; Oktaviani, Anggi; Sundari, Tari; Sari, Revi Puspita; Tranado, Hengki; Rohani, Tuti; Azissah, Danur (Universitas Dehasen Bengkulu, 2025)
Gastritis is a state of inflammation or bleeding of the gastric mucosa that can be acute and chronic (Aspitasari & Taharuddin, 2020). The public generally knows gastritis as an ulcer disease, which is a disease that they think is not a big problem, gastritis occurs at all ages ranging from children, adolescents, adults to the elderly (Jannah, 2020). Gastritis can be treated with pharmacological or non-pharmacological treatment. The purpose of the counseling that our group carried out was to provide education about gastritis to the people of Hamlet 2 in Sumber Sari village. It is hoped that the counseling carried out by our group can overcome and reduce the number of gastritis sufferers in hamlet 2 of Sumber Sari village.